Um estudo sobre a eficiência dos compiladores da linguagem GO com o auxilio de algoritmos genéticos - Medeiros, Raniere Fernandes de (2018)
The Go language is one of the newer current languages with an increasing popularity in the software industry. It is deﬁned by a speciﬁcation and implemented by two compilers with diﬀerent proposals to ensure that the speciﬁcation is correct and complete. The gc compiler focuses on quick compilation and few optimizations while gccgo focuses on using GCC optimizations without worrying about the compiling time that is spent. This work proposes a study with the objective of constructing a genetic algorithm that assists in the identiﬁcation of situations that gccgo can be more eﬃcient than the Go Compiler. Results show that the Go Compiler is on average 24.7 times more performance at runtime and with an average executable ﬁle size of 33.86 times greater than the generated gccgo executable using a subset of optimization options.